In vitro synergy of oxacillin and gentamicin against coagulase‐negative staphylococci from blood cultures of neonates with late‐onset sepsis. Issue 9 (7th January 2013) - Brilene, Tatjana; Soeorg, Hiie; Kiis, Merilin; Sepp, Epp; Kõljalg, Siiri; Lõivukene, Krista; Jürna‐Ellam, Marika; Kalinina, Jelena; Štšepetova, Jelena; Metsvaht, Tuuli; Lutsar, Irja
Abstract : Coagulase‐negative staphylococci (CoNS) are the leading cause of late‐onset sepsis (LOS) in neonates. Increasing resistance of CoNS to beta‐lactams and aminoglycosides has led to widespread use of vancomycin, which in turn may lead to resistance to vancomycin. Thus, combination therapy of LOS has been advocated. We aimed to determine the interaction of oxacillin and gentamicin against CoNS. In 2005, 34 isolates of oxacillin‐ and gentamicin‐resistant CoNS were obtained from blood samples of neonates with LOS. Combination effect was tested using the checkerboard method, E‐test with the other antibiotic incorporated in the medium (E‐test‐1) and two E‐test strips placed in a cross‐formation (E‐test‐2). Of 34 isolates 61.8%, 53% and 73.5% revealed synergy or an additive effect when tested by the checkerboard method, E‐test‐1 and E‐test‐2, respectively. Results of all three tests were concordant for six (17.6%) isolates, four showing synergy, and two indifference. Our in vitro results support that combination therapy with penicillinase‐resistant penicillin and aminoglycoside can be an alternative to vancomycin.